Development of Novel ICH Compliant Method for Estimation of Ethanol Content in Traditionally Fermented Ayurvedic Formulations - Maithani, Mukesh; Gupta, Vikas; Bansal, Parveen; Singh, Harpreet; Raturi, Richa (Current Traditional Medicine, 2019)
Background: Due to lack of stringent regulations and standards from regulatory authorities, Ayurvedic formulations available in the market are not properly standardized and assessed for their quality. Asava and arishta are very important fermented and commonly used dosage forms of Ayurveda. Information on the quantitative parameters of the ayurvedic fermented preparations is very poor. These formulations contain naturally selfgenerated alcohol that acts as the medium for extraction of active ingredients of the herbs. Hence alcohol content becomes a point of concern as well as an important parameter for standardization of the asava and arishta and it becomes important for manufacturers to mention alcohol content on the label. In addition, as per ASU GMP guidelines, it is mandatory to assess the accurate ethanol content to ensure the quality of the product. However manufacturers used to escape to comply with the guidelines because of complexity, cost and time consuming available methods. Hence there was a need to develop a novel method. Objective: This study is intended to develop a simple, efficient, less time consuming, economic and accurate gas chromatography method and estimate the ethanol content in marketed ayurvedic formulations of asava and arishta. Methods: The GC system (Nucon 5700 Gas Chromatograph) fitted with flame ionization detector was used in the present study. A capillary packed column (2m length and 3.170mm diameter) with stationary phase made up of WHP having 0.14mm in mesh size with nitrogen carrier gas was, used and the data were acquired through Winchrom software. Results and Discussion: The retention time for ethanol was found to be 1.53min. The correlation coefficient (r2) of ethanol was found to be 0.9990. The ethanol content obtained by the proposed method was found to be between 3.05% and 11.53%. Conclusion: The study presents a simple and validated gas chromatographic method for estimation of ethanol content in herbal formulations. The developed method was found to be specific, accurate, precise and rugged. The method has been successfully applied for the analysis of marketed ayurvedic formulations.
Keywords: fermented ayurvedic formulations